A informação como fundamento para otimização dos serviços administrativos da coordenação do curso de graduação em biblioteconomia da UFPB - Honorato, Gersonilson Ribeiro (2012)
The Information science plays primary function in the information society, in that it wherein cares with the scientific research in various fields of knowledge, because the success of the information depends on what you know and not of what you have. In this sense the research aimed to analyze the information services of the Undergraduate Course in Librarianship at the Center for Applied Social Sciences, Federal University of Paraíba (CGB / CCSA / UFPB) a order to provide guidelines and standards administrative that can subsidize on development an communication instrument and information to meet the current demands of the student body. The survey was conducted with a sample of 202 students, divided among the ten existing classes of the course. Data collection was conducted through a questionnaire administered by the researcher of this study. The results showed that products and information services such as: student manual; guide to internships; blog and informative newspaper are indispensable to answer their informational needs. And finally, further suggests that Coordination in motivate their employees to build capacity, absorbing values as: being server, administrative management, behavioral skills in customer service, which can be realized through the Rectory Pro of Personnel Management (PROGEP), through the Coordination of Personnel Development (CDP) and the Division of Vocational Education and Training (DECP). Thus, it is possible that the information produced, accessed and shared to achieve their goals.